Perkembangan Peran Media Sosial sebagai Sumber Berita: Peluang dan Ancaman - Cendera Rizky Bangun (Ultimacomm: Jurnal Ilmu Komunikasi, 2017)
As new media emerge and replace the popularity of conventional media, people use social media not only as medium to socialize, but also increase its role as news source or news outlet. A generational divide has always existed within news. The older people tend to choose TV and newspaper as their primary news source meanwhile research conducted by Reuters in 2015 showed that younger audiences that grown up in digital era, exhibiting very different behaviors and increasingly expect the news to come to them through online channels and in new formats. This makes social media become the opportunities and also threats to some news companies. What should the media do in order to survive? Does the generation gap influence the media to use both traditional and digital or social media? Some online media even put their headlines and link in Facebook and Twitter as news outlet, so people can just click the link and go to their websites. Methodology used in this research is qualitative with data gathered from focus group discussion and interview. The result of the study expected to show how the generation gap creates different media consumption and the need for news corporation to change their pattern in order to survive. Keywords: Social media, news outlet, new media